The Evaluate in Aboveground Carbon Storage Changes Over 1 Year Period in Reforestation Area f Luang Prabang Province - SALIMATH, Pone; PHONCHALUEN, Sengkham; BOUAPHAKEO, Pazeun (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study was conducted in the forest restoration area of Hongsa Power Company Limited, located in Luang Prabang Province. Data were collected from seven permanent sample plots (20 × 20 m) during 2023 and 2024 to examine changes in aboveground biomass carbon sequestration of standing trees. In 2024, a total of 292 standing trees were recorded, averaging 1,043 trees per hectare and representing 39 different species. The average aboveground biomass accumulation was 62.65 tons per hectare, with carbon storage of 31.32 tons per hectare and carbon dioxide (CO₂) absorption of 114.85 tons per hectare per year. Compared to 2023, the biomass increased by an average of 7.92 tons per hectare per year, carbon sequestration rose by 3.96 tons per hectare per year, and CO₂ absorption increased by 14.53 tons per hectare per year. At the individual plot level, all sample plots showed increased carbon sequestration rates. Plot 7 had the highest increase, followed by Plots 4, 2, 6, 1, 3, and 5, with respective increases of 5.64, 5.39, 4.93, 4.90, 3.40, 2.51, and 0.96 tons per hectare per year.